2020
DOI: 10.3389/fonc.2020.574277
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CYP2J2 to Enhance the Anti-Glioma Efficacy of Cannabinoid Receptor 2 Stimulation by Inhibiting the Pro-Angiogenesis Function of M2 Microglia

Abstract: Enhancing the therapeutic efficacy of anti-tumor drugs is essential for cancer management. Although cannabinoid receptor 2 (CB2R) stimulation exerts anti-tumor action in glioma cells by regulating cellular proliferation, differentiation, or apoptosis, selective CB2R agonist alone does not achieve a satisfactory therapeutic outcome. Herein, we aimed to evaluate the possible strategy for enhancing the anti-glioma efficacy of JWH133, a selective CB2R agonist. In this study, immunofluorescence and qRT-PCR were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…For example, overexpression of CYP2J2 is beneficial in the treatment of diabetes [10] and in the reduction of cardiac hypertrophy 12 BioMed Research International [27]. However, CYP2J2 is significantly expressed in various tumors [28,29], including KIRC, but it remains unknown if CYP2J2 overexpression in KIRC is beneficial or harmful. Therefore, we investigated the correlation between CYP2J2 expression and KIRC using various databases, including Oncomine, GEPIA DriverDBv3, and TIMER databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, overexpression of CYP2J2 is beneficial in the treatment of diabetes [10] and in the reduction of cardiac hypertrophy 12 BioMed Research International [27]. However, CYP2J2 is significantly expressed in various tumors [28,29], including KIRC, but it remains unknown if CYP2J2 overexpression in KIRC is beneficial or harmful. Therefore, we investigated the correlation between CYP2J2 expression and KIRC using various databases, including Oncomine, GEPIA DriverDBv3, and TIMER databases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of CYP2J2 is beneficial in the treatment of diabetes [ 10 ] and in the reduction of cardiac hypertrophy [ 27 ]. However, CYP2J2 is significantly expressed in various tumors [ 28 , 29 ], including KIRC, but it remains unknown if CYP2J2 overexpression in KIRC is beneficial or harmful.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we detect an increase in angiogenesis and a decrease in MBP loss at 14 days after cerebral ischemia in the ADSC-EVs treated group compared to the PBS control. It is well established that M2 microglia promote angiogenesis [52,53]. For instance, culture supernatant of M2 microglia promotes angiogenesis in vitro in human brain microvassal endothelial cells (HBMECs) [50].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, THC induced the profile of Th2 polarisation, resulting in an increase in Th2-associated cytokines and a downregulation of Th1-related cytokines [160]. Finally, another investigation showed that the CB 2 receptor-activating effect of cannabinoids attenuates its own antitumour effect by promoting M2 polarisation of microglia/tumour-associated macrophages (TAMs), causing a proangiogenic effect of M2 microglia [161].…”
Section: Effect Of Cannabinoid Compounds On Tumour-immune Interactionsmentioning
confidence: 99%